Complementing existing CHP plants using biomass for production of hydrogen and burning the residual gas in a CHP boiler. Issue 6 (2nd November 2017) - Naqvi, Muhammad; Dahlquist, Erik; Yan, Jinyue
ABSTRACT: Biorefinery systems at combined heat and power (CHP) plants represent numerous technical, economic and environmental benefits by utilizing the existing biomass handling infrastructure and producing biofuels together with heat and power. This study evaluates the economic feasibility of integrating biomass gasification to an existing CHP plant. Integration includes biomass gasification with downstream processing of the synthesis gas to remove particles and tars, condense out water, remove CO2 and use membrane filtration (polyamide membrane) to extract hydrogen. The separated residual gas components are utilized as extra fuel to the boiler in the CHP plant. Approximately 58.5 MWth of synthesis gas can be produced from a 90 MWth plant that represents 16.4 MWth of hydrogen. The rest of the heating value of produced synthesis gas (in the form of methane and carbon monoxide) is utilized for heat and power production. From an economic perspective, the production cost of hydrogen is estimated to be 0.125–0.75 €/kg. This can be compared to the US governments goal that H2 produced by wind power plus electrolyzers should have a maximum cost of 2.8–3.4 €/kg. The lower cost is for a unit operating at 3 bar and assuming that the costs are split between H2 and the syngas residue that is combusted, while the higher prices assume an atmospheric gasifier and all costs are put on the H2 produced.